An experimental study on the pollen particle blocking efficacy of a barrier nasal mask - Zhang, Yan; Lu, Na; Zhao, Yuxiang; Wang, Jinping (Frontiers in Medicine, 2025)
ObjectiveTo explore the blocking effect of a barrier nasal mask composed of bionic nasal hair combined with a blocking gel on allergen particles in a 1:1 3D-printed nasal cavity model and to provide new ideas for the clinical prevention and treatment of allergic rhinitis.MethodsA 1:1 scale 3D-printed nasal cavity model was constructed, and dust-free paper was placed at specific anatomical locations within the model. The experimental group was defined as those wearing a nasal mask, whereas the control group did not wear a nasal mask. A simple breathing bag was used to simulate normal respiration, and a pneumatic nebulizer was employed to introduce stained Artemisia annua pollen. The simulated breathing experiments were conducted for 15 min and 30 min. The degree of staining on the dust-free paper in both groups was observed and scored.ResultsAt 15 min, the median (25th, 75th percentiles) total scores for all anatomical sites in the nonblocking group and blocking group were 3 (2, 4) and 0 (0, 1), respectively (Z = −9.094, p < 0.001). At 30 min, the total scores of the two groups were 4 (2, 5) and 1 (0, 2), respectively (Z = −9.062, p < 0.001). Additionally, the comparison of scores at all other individual anatomical sites revealed p < 0.001.ConclusionThis barrier nasal mask can effectively reduce pollen particle deposition at various anatomical sites in the nasal cavity. The crossover test using the same model verified the reliability of its blocking efficacy, which suggests that it is a potential innovative intervention for the prevention of allergic rhinitis.